1996
DOI: 10.1097/00004424-199607000-00006
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Evaluation of the Effectiveness of Different Methods of Displaying Three-Dimensional Information with Medical X-Ray Images

Abstract: It was found that rotational stereoscopic fluoroscopy is feasible and is an effective way of portraying 3-D information using x-rays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This qualitative observation matches research findings on stereoscopic display techniques in X-ray technology8 and is also consistent with the differences between static and dynamic stereoacuity described by Mathias and Rudolf Sachsenweger 17. Stereoscopic movies also showed an increase in apparent image sharpness compared to stereoscopic stills, which may be explained by Shipley’s description of stereoscopic contour integration over blur 18.…”
Section: Discussionsupporting
confidence: 90%
“…This qualitative observation matches research findings on stereoscopic display techniques in X-ray technology8 and is also consistent with the differences between static and dynamic stereoacuity described by Mathias and Rudolf Sachsenweger 17. Stereoscopic movies also showed an increase in apparent image sharpness compared to stereoscopic stills, which may be explained by Shipley’s description of stereoscopic contour integration over blur 18.…”
Section: Discussionsupporting
confidence: 90%
“…Studies with random 3D dot patterns found that motion enabled observers to distinguish between dots which they were otherwise unable to do (Nakayama, 1985). Similarly Hardy et al (1996) found that rotation was important for recognition of 3D X-ray images. These findings underpin H5-7: voxels are subject to lighting effects hence motion is less necessary to delineate between different parts of an object, and thus will have a bigger impact on point clouds than voxels.…”
Section: Hypothesesmentioning
confidence: 94%
“…Studies that can be performed with RFT include antegrade pyelography, evaluation of UPJ or UVJ obstruction. [3637] Non-urological applications include percutaneous transhepatic cholangiography, evaluation of recto-urethral fistulae, anal atresia and comminuted fractures. The radiation exposure of an RFT study is one-sixth that of a CT scan [Figure 6f and 9b].…”
Section: Rotational Fluoroscopic Tomographymentioning
confidence: 99%